Trasformazioni dell’Apocalisse in Mario Vargas Llosa: dal fanatismo de La guerra del fin del mundo al cuore di tenebra de El sueño del celta (Altre Modernità, 2013)
The paper aims to underline that in the Peruvian writer there is a double reading of the apocalypse. In the novel La guerra del fin del mundo the apocalypse is represented as a religious, political, environmental disruption of a world: the apocalypse is caused by ignorance and poverty, wich are the culture media of fanaticism, racism and religious dogmatism. In the last novel El sueño del celta, the apocalypse is instead caused by the lust for power and the abyss of evil present in the human being.